NÓRMASE EN EL CÓDIGO DEL TRABAJO, LA FORMALIZACIÓN DE LA PRUEBA ADJUNTO A LA DEMANDA, EN GARANTÍA DEL PROCEDIMIENTO ORAL - Mendoza Aguirre, María Edith (2016)
Constitutional rights and guarantees to be observed effectively in a work process work, is one of the expressions of a Constitutional State of Rights and Social Justice, seeking, which comply with the rights and guarantees of workers, protecting and applying the Treaties and International Conventions on Human Rights and the International Labour Organization. The constitutional principles that clearly states our Constitution are of a higher order, which necessarily must be observed, more to the guarantees of the rights of labor, labor-management relations, and as a fundamental part in the development of judicial process that ensures the due process for effective judicial protection as in the case of workers. The test is a means of demonstrating the truth of a claim, the existence of a fact or an event, and must be assessed by the judge with strict sense of logic and reason, the Code of Civil Procedure, has that the evidence must be assessed in accordance with the principles of sound criticism, same that will be integrated by the rules of logic and experience of judges, it is the judge's reasoning with logic and experience, free of arbitrariness in the reasonableness of the litigants. The reasoning, becomes the product of a derivation of a set of propositions such that one conclusion is derived from the other premises, which are - 5 - - 5 - considered as explanatory elements of the first, the experience is a sense of control that integrates cognitive society as a whole, and in a work process, the test must be subject to the facts and acts that are valued in the process, and that formality is substantiated by the general principle of due process